n Ondersoek na die instelling en invloed van byvoordele op werkersgroepe - De Klerk, P. B.(Petrus Benjamin) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Com.) -- Universiteit van Stellenbosch, 1967.